AN IN-DEPTH EXAMINATION OF THE POLITICAL LANDSCAPE IN INDONESIA:UNRAVELING COMPLEXITIES IN THE EVOLVING DYNAMICS OF GENERAL ELECTIONS, POLITICAL PARTY EVOLUTION, AND MULTI-DIMENSIONAL CIVIC ENGAGEMENT - Agustinus F. Paskalino Dadi; Dedy Ari Nugroho; Eduard M. J. Kocu, Renida J. Toroby, Diego Romario De Fretes (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This comprehensive research examines Indonesia's intricate political landscape, meticulously unraveling the multifaceted complexities that define the evolving dynamics of general elections, political party evolution, and multi-dimensional civic engagement. By synthesizing a diverse literature, this study navigates the historical trajectories, offering insights into critical events that have shaped the nation's political identity. An in-depth analysis of the electoral processes explores the nuanced mechanics and transformations, shedding light on the adaptive strategies employed by political parties. In parallel, the research explores the dynamic evolution of political parties, tracing their historical development and ideological recalibrations. From grassroots activism to media influence, the study ventures into the multi-dimensional realm of civic engagement, dissecting the intricacies of societal participation. By examining the interplay between political parties and broader political changes, the research provides a holistic understanding of Indonesia's socio-political. This exploration identifies the challenges inherent in this complex political landscape and sheds light on opportunities for enhancing citizen participation. The findings contribute to a nuanced comprehension of Indonesia's political dynamics, offering valuable insights for scholars, policymakers, and practitioners alike. Through an interdisciplinary approach, this research aims to foster a deeper understanding of the historical, institutional, and societal dimensions that collectively shape Indonesia's unique political identity.